AKIBAT HUKUM SURAT KUASA DIREKSI YANG DIPALSUKAN TERHADAP KREDIT YANG TELAH DICAIRKAN (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 4575 K/PDT/2022) - Anam, Novarani Caltiara; Nurdin, Aad Rusyad (Universitas Ekasakti, 2023)
It is important to be careful when the directors assign the authority of substitution to someone else who will represent the company. The Directors shall set down in the Power of Attorney in specific and definite terms the scope of the legal activities authorized by the Power of Attorney. This does not, however, exclude the chance that the person who received the power of attorney might abuse that authority and cause damages for the agent of that power of attorney. In the Decision of the Supreme Court Number 4575 K/PDT/2022, the notary, who was the party who made the deed of power of attorney for the directors, bears responsibility for the legal ramifications of a forged directors' power of attorney on credit that has been disbursed. A normative-juridical research methodology with a case study approach was utilized to examine Supreme Court Decision Number 4575 K/PDT/2022. According to the study's findings, the credit agreement remained legally enforceable for the parties even though the power of attorney for directors was declared illegal because it failed to satisfy the subjective criteria for agreement validity. Therefore, even though the notary who created the forged power of attorney is not criminally liable, he is nonetheless held civilly liable for any losses brought on by the forged document.